2021
DOI: 10.3390/ejihpe11030067
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Validation Study of the Intrinsic Religious Motivation Scale and the Centrality of Religiosity Scale for the Portuguese Population

Abstract: Religion is a construct widely present in most people’s lives. Religious motivations, either intrinsic or extrinsic, as well as religious centrality, are crucial aspects of religion. In the Portuguese population, there are no validated instruments to assess these aspects of religion. Accordingly, this study intends to validate the Intrinsic Religious Motivation Scale (IRMS) and the Centrality of Religiosity Scale (CRS) for the Portuguese population. This is a validation study whose sample consists of 326 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…Our results are quite similar from those of Liu and Koenig (2013), who found a two-factor solution; however, the study by these authors was carried out in a non-Western and non-Christian society (China), unlike our study. Also, Araújo et al (2021) found two factors in their preliminary study for the Portuguese population. Hafizi et al (2015) assessed the psychometric properties of the Farsi version of the Hoge Intrinsic Religiosity Scale and found a two-factor solution.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are quite similar from those of Liu and Koenig (2013), who found a two-factor solution; however, the study by these authors was carried out in a non-Western and non-Christian society (China), unlike our study. Also, Araújo et al (2021) found two factors in their preliminary study for the Portuguese population. Hafizi et al (2015) assessed the psychometric properties of the Farsi version of the Hoge Intrinsic Religiosity Scale and found a two-factor solution.…”
Section: Discussionmentioning
confidence: 98%
“…The scoring of one’s responses differentiates three groups: very religious individuals, religious individuals, and non-religious individuals. This scale has been found to have a Cronbach’s alpha (α) coefficient of 0.85 [ 29 , 30 ]. The CRS-5 has been translated to Spanish by study personnel for use in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The results obtained confirm the existence of a population-adjusted model, allowing the conclusion that the instrument is reliable for assessing the constructs studied. The validation of IRMS and CRS for the Portuguese population is very important, as it provides researchers in the field with valid instruments and psychometric qualities to conduct research in religion and religiosity (Araújo, 2021).…”
Section: Introductionmentioning
confidence: 99%